Leveraging the Attributes of Mucor hiemalis-Derived Silver Nanoparticles for a Synergistic Broad-Spectrum Antimicrobial Platform - Aziz, Nafe; Pandey, Rishikesh; Barman, Ishan; Prasad, Ram (Frontiers in Microbiology, 2016)
Driven by the need to engineer robust surface coatings for medical devices to prevent infection and sepsis, incorporation of nanoparticles has surfaced as a promising avenue to enhance non-fouling efficacy. Microbial synthesis of such nanoscale metallic structures is of substantive interest as this can offer an eco-friendly, cost-effective and sustainable route for further development. Here we present a Mucor hiemalis-derived fungal route for synthesis of silver nanoparticles, which display significant antimicrobial properties when tested against six pathological bacterial strains (Klebsiella pneumonia, Pseudomonas brassicacearum, Aeromonas hydrophila, Escherichia coli, Bacillus cereus and Staphylococcus aureus) and three pathological fungal strains (Candida albicans, oxysporum, and Aspergillus flavus). These antimicrobial attributes were comparable to those of established antibiotics (streptomycin, tetracycline, kanamycin and rifampicin) and fungicides (amphotericin B, fluconazole and ketoconazole), respectively. Importantly, these nanoparticles show significant synergistic characteristics when combined with the antibiotics and fungicides to offer substantially greater resistance to microbial growth. The blend of antibacterial and antifungal properties, coupled with their intrinsic “green” and facile synthesis, makes these biogenic nanoparticles particularly attractive for future applications in nanomedicine ranging from topical ointments and bandages for wound healing to coated stents.